Satellite-based approach for multi-temporal PM10 analysis over Malaysia - Ahmad, Asmala; Hashim, Mazlan; Ayof, Mohd Nizam; Budi, Agus Setyo (2005)
This study aims to analyse one of the haze major constituent, particulate matter sizing less than 10 micron (PM 10) from space-borne platform. Seven dates of NOAA-14 AVHRR satellite were successfully recorded for this purpose. These remotely sensed data represented the seven days during the September 1997 thick haze episode in Malaysia. Five locations of air pollution station were selected where PM10 has been measured. Visible (0.58 - 0.68 m) and Near Infrared (0.725 - 1.00 m) of AVHRR band was utilised for this purpose. Relationship between the satellite reflectance and the corresponding PM 10 ground measured API was determined using regression analysis. Variation of PM 10 concentration for seven days was then analysed using the obtained model. Finally, accuracy of the result was assessed using RMSE technique. The result proven that remote sensing technique using NOAA-14 AVHRR data was capable of quantifying PM 10 concentration spatially and continuously. Complementarily, DMSP and Earth Probe TOMS satellite data were also used as comparison.